Moralisation and criminalisation: a socio-political history of the expulsion of foreigners in Belgium (1830-1952). (2017) - Crosby, Andrew
This article analyses through an historical lens how the policy of expulsion of foreigners in Belgium was born and has been transformed over time. Relying on the analysis that the rise of state intervention in the last quarter of the 19th century elevated nationality as a demarcation criterion, I say that these changes can only fully be understood if we take into account the ideological origins and use of the policies. Hence, the paradigm of the state of exception is used to describe the policies that specifically targeted political opponents and destitute foreigners. Lastly, following the theory of degradation ceremonies, I analyse how framing the foreigner as an unethical subject was an important step in legitimising the exceptional power of expulsion.